The fall of five - Lore, Pittacus (Penguin Books, 2014)
I thought things would change when I found the others. We would stop running. We would fight the Mogadorians. And we would win. But I was wrong. Though we came together, we barely escaped with our lives. And now we hide. The six of us are powerful - but not strong enough to take on an army. We haven't discovered our full legacies. We haven't learned to work together. And time is running out, because we need to find number five before they do. This battle is far over...